1995
DOI: 10.1093/infdis/171.3.739
|View full text |Cite
|
Sign up to set email alerts
|

Presence Of Bactericidal/Permeability-Increasing Protein In Disease: Detection By Elisa

Abstract: A sandwich ELISA was developed specific for human bactericidal/permeability-increasing protein (BPI), using Mg++ ions to abrogate disturbance by lipopolysaccharide of BPI measurement and to prevent aspecific adherence of BPI to solid phase. In fresh EDTA or heparinized plasma of healthy volunteers BPI was not detectable, whereas in serum BPI was present, indicating that coagulation activates polymorphonuclear leukocytes to release BPI. Furthermore, BPI was present in plasma of critically ill intensive care uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Several clinical studies have demonstrated LPS-response-mediating proteins to amplify or counteract the response to endotoxins in disease (Opal et al 1994;Dentener et al 1995). Previously we studied the LBP and BPI in plasma of grain workers exposed to grain dust and endotoxin (<10 ng/m 3 ) and found no change in these proteins or in the ratio.…”
Section: Discussionmentioning
confidence: 92%
“…Several clinical studies have demonstrated LPS-response-mediating proteins to amplify or counteract the response to endotoxins in disease (Opal et al 1994;Dentener et al 1995). Previously we studied the LBP and BPI in plasma of grain workers exposed to grain dust and endotoxin (<10 ng/m 3 ) and found no change in these proteins or in the ratio.…”
Section: Discussionmentioning
confidence: 92%
“…BPI, another PLTP-related protein that neutralizes LPS, is a potent inhibitor of CD14-dependent cell activation by endotoxins, has direct Gram-negative bacterial killing properties, and enhances bacterial phagocytosis (36,51). Although BPI is normally an intracellular factor that is produced and stored in neutrophils and is not detected in plasma under normal physiological conditions (52), the overexpression of circulating forms of BPI or BPI fragments in mice was shown to provide protection from lethal endotoxemia (53,54). In humans, the injection of recombinant BPI was found to be effective in decreasing morbidity and functional outcomes in children with severe meningococcemia but with no significant decrease in mortality (55).…”
Section: Discussionmentioning
confidence: 99%
“…The following ELISAs were performed according to the instructions of the manufacturer and/or as described: D-dimer, F1ϩ2 prothrombin fragment and thrombin-antithrombin (TAT) complexes (all Dade Behring), tPA (Asserachrom tPA, Diagnostics Stago), PAI-1 (Monozyme), and Elastase-␣1-antitrypsin complex concentrations were measured with an ELISA modified from a radioimmunoassay (RIA) procedure as described, 28 bactericidal permeability-increasing protein (BPI), 29 von Willebrand Factor (vWF) (Dako), soluble E-selectin (Diaclone), tumor necrosis factor (TNF)-␣, IL-6, IL-10, and IL-8 (all Central Laboratory of the Netherlands Red Cross Blood Transfusion Service). PAP complexes were measured by RIA as described.…”
Section: Assaysmentioning
confidence: 99%